Impact of social-context on the relationship between achievement-motivation and anxiety, expectations or social conformity - Anne Marie Fontaine (1991)
This study analyses the impact of life contexts (socioeconomic status and area of residence) and sex of a child on the relationship between achievement motivation at school and other variables such as: anxiety (facilitating, debilitating), social conformity and success expectations. These variables are traditionally associated with regard to the 'expectancy-value' models. The sample of 288 pupils was selected from approx. 4500 sixth grade Portuguese students through a multifactorial design. The four selection factors were: socioeconomic status, area of residence, sex and motivational level of the subjects. Results from the multivariate and univariate analysis of variance indicate that the more motivated pupils showed higher facilitating anxiety, lower debilitating anxiety, were more conformist and expressed higher success expectation. These results, however, would vary according to the life context and the sex of the child, and are inverted in some cases. Some elements of the context that could explain the above mentioned results are discussed, considering the cognitive and affective variables as regulators of the social development of achievement motivation at school. (c) 1991.